1996
DOI: 10.1016/s0092-8674(00)81267-2
|View full text |Cite
|
Sign up to set email alerts
|

cul-1 Is Required for Cell Cycle Exit in C. elegans and Identifies a Novel Gene Family

Abstract: The gene cul-1 (formerly lin-19) is a negative regulator of the cell cycle in C. elegans. Null mutations cause hyperplasia of all tissues. cul-1 is required for developmentally programmed transitions from the G1 phase of the cell cycle to the GO phase or the apoptotic pathway. Moreover, the mutant phenotype suggests that G1-to-S phase progression is accelerated, overriding mechanisms for mitotic arrest and producing abnormally small cells. Significantly, diverse aspects of cell fate and differentiation are una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
369
5
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(381 citation statements)
references
References 40 publications
6
369
5
1
Order By: Relevance
“…J.R.L. is a Damon Runyon Fellow supported by the Damon Runyon Cancer Research (DRG 2061-10 EM (1996) cul-1 is required for cell cycle exit in C. elegans and identifies a novel gene family. …”
Section: Acknowledgementsmentioning
confidence: 99%
“…J.R.L. is a Damon Runyon Fellow supported by the Damon Runyon Cancer Research (DRG 2061-10 EM (1996) cul-1 is required for cell cycle exit in C. elegans and identifies a novel gene family. …”
Section: Acknowledgementsmentioning
confidence: 99%
“…The other two cullin homologous genes were designated pcu3 þ (SPAC24H6.03) and pcu4 þ (SPAC3 A11) as the predicted products of the two genes showed the highest homology to cullin-3 and cullin-4, respectively (42% and 40%, respectively, Kipreos et al 1996). Budding yeast contains, in addition to Cdc53, two ORFs which are cullin members.…”
Section: Cullin Homologues In the Fission Yeast Genomementioning
confidence: 99%
“…Cdc53 acts as a scaffold for the SCF complex (Patton et al 1998a) and is also conserved. Furthermore, Cdc53 comprises a large protein family called cullin (Cdc53 is a cullin-1 homologue and humans have at least six cullin members, Kipreos et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, we reported that a major target of NEDD8-ylation is Hs-Cul-4A (Osaka et al, 1998), but it has been reported so far that human cullins consist of six family proteins termed Cul-1, Cul-2, Cul-3, Cul-4A, Cul-4B, and Cul-5 (Kipreos et al, 1996). It remains obscure whether NEDD8 is also ligated to other Hs-Cul-family proteins in addition to Cul-4A.…”
mentioning
confidence: 99%